Exlibris Th. S. Wróblewskiego A. Półtawski. - Półtawski, Adam (1881-1952) (1931)
W obramowaniu na tle obfitych labrów herb. Niżej na wstędze napis: Exlibris Th. S. Wróblewskiego. Sygn. aut. w obrębie kompoz.